Thin plate element for applied element method. (December 2019) - Christy, D. Lincy; Pillai, T.M. Madhavan; Nagarajan, Praveen
Abstract: Applied Element Method (AEM) is an efficient method for numerical analysis of structures. It is capable of analyzing the structure up to collapse. In AEM, the structure is modelled as a group of rigid elements connected by springs. It has the benefit of lesser processing time and memory requirement when compared to Finite Element Method. It is also able to track crack propagation more realistically. To extend the advantages of AEM to the analysis of thin plate structures, thin plate element has to be developed. This is done in this paper. Being a rigid body method, AEM does not consider Poisson's ratio in its basic formulation. As Poisson's ratio plays a major role in the behavior of plate structures, the method to bring in Poisson effect in thin plate element is discussed. The procedure to determine displacements, strains, stresses and stress resultants are explained. The mass matrix for thin plate element is also found. To validate the thin plate element, both static and dynamic analyses are carried out. The analyses gave reliable results which show the efficiency of the thin plate element of AEM.